2019
DOI: 10.1111/ipd.12493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of defective restorations and factors associated with re‐intervention in primary teeth: A retrospective university‐based study

Abstract: Aim This retrospective study investigated the prevalence of defective restorations in a public dental service and factors associated with re‐intervention in primary teeth. Design The sample consisted of all clinical records (census) of children presenting restorations in primary teeth, who had undergone dental treatment in a public set during 1‐year period. For analysis, only restorations presenting defects related to esthetic, functional, or biological reasons at first clinical examination were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The diagnosis of recurrent caries is the main reason for restoration replacement 15 . It has been shown that the presence of recurrent caries influences the decision to intervene, and this leads to restoration replacement in most cases 16 . Although recurrent caries are histologically similar to primary caries, the clinical diagnosis for evaluating the presence of caries or staining around restoration margins is a challenge for dentists and it is a subjective process.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of recurrent caries is the main reason for restoration replacement 15 . It has been shown that the presence of recurrent caries influences the decision to intervene, and this leads to restoration replacement in most cases 16 . Although recurrent caries are histologically similar to primary caries, the clinical diagnosis for evaluating the presence of caries or staining around restoration margins is a challenge for dentists and it is a subjective process.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon affects the development of the carious process in the surrounding hard tissues, both enamel and dentin, which in turn increases the risk of complications from the pulp and then leads to the need to replace the filling [1,2]. Replacement of the filling is associated with the necessity to widen the removed margins of the tooth tissue, which can then lead to further cycles of intervention and is associated with increased treatment costs [3]. Etiopathogenesis of secondary caries does not differ from primary caries and depends mainly on host-related factors such as diet and oral hygiene [4].…”
Section: Introductionmentioning
confidence: 99%
“…These substances are naturally found in many fruits and are manufactured from natural raw materials, such as lignocellulosic biomass (xylitol), starch (sorbitol), and glucose (erythritol) [14,15]. In vitro, in vivo, and clinical studies have consistently demonstrated the safety of these substances [1][2][3][4], which has been confirmed by recommendations issued by the WHO/FAO (World Health Organization/Food and Agriculture Organization of the United Nations) Joint Committee of Experts on Food Safety in over 60 countries around the world [16].…”
Section: Introductionmentioning
confidence: 99%
“…8 A retrospective study demonstrated a 37.7% failure rate among restorations on primary teeth. 9 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%